Diametric growth and time of passage in an Atlantic Forest fragment under forest recovery - Lafetá, Bruno Oliveira; Silva, Alan Reges Ferreira da; Vieira, Diego dos Santos; Reis, Mateus dos; Ribeiro, Carlos Henrique Lopes; Guimarães, Luis Henrique de Andrade (Revista de Ciências Agroveterinárias, 2024)
Scientific investigations on the dynamics of plant communities promote appropriate strategies for management of natural forests, with conservationist or sustainably exploratory purposes. This research aimed to evaluate accuracy of regression models to project diameter growth and calculate passage time by diametric class of stems in an Atlantic Forest fragment under recovery. The work was carried out in a fragment of 2.53 ha in São João Evangelista municipality (MG). Inventory was performed at 80 and 104 months after starting the recovery process. Annual periodic increment (API) information in diameter was used to calculate passage time and relative age. IPA estimate ranged from 1.5 to 1.7 cm year-1 (passage time of 3 years in 5 cm amplitudes) in the range of 10 to 25cm in diameter. Relative age for the stems to reach 5 cm in diameter was approximately 5 years. It is concluded that the logistic and Curtis models, adapted for the IPA estimation, are efficient for analysis of passage time in the studied fragment. Fragments during forest recovery may exhibit similar growth rates between diameter classes.